Diffusion of electric vehicles and their flexibility potential for smoothing residual demand: A spatio-temporal analysis for Germany - Fabian Arnold; Arne Lilienkamp; Nils Namockel (Institute of Energy Economics at the University of Cologne (EWI), 2023)
The transformation of the energy system causes increasing stress on distribution grid components. However, rexible EV charging, if incentivized adequately, can help mitigate this impact by reducing peaks in loads and feed-in. A comprehensive regional analysis is necessary to understand the potential of EV charging rexibility for reducing peaks on regional and national levels. To this end, we estimate regional residual demand time series for Germany for the years 2019, 2030 and 2045. We focus on modelling private EV diffusion via sigmoid functions and deriving driving and charging proîoles based on micro mobility data. Further, we distinguish two deployment schemes for EV rexibility: (1) all EVs contribute to rattening the national residual load curve; (2) local EVs contribute to rattening regional residual load curves. We îond that the residual load curves change structurally as positive and negative peaks in residual demand increase over the years on the regional and national levels. Although the absolute rexibility potential of EV home charging increases with the number of vehicles, its marginal utility to reduce load peaks declines. Especially in load-dominated regions, the national deployment of rexibility can result in higher regional demand peaks compared to a scenario without charging rexibility. The two approaches of rexibility activation can be contradictory in their effects: While regional incentivization is less efficient in reaching the smoothing in the national residual demand curve, national incentivization can even lead to increased strain on the local level.
Keywords: C61; D47; O33; Q41; Q48; 330; Flexibility; Electric vehicles; Residual load; Energy transition; Charging proîoles